Space debris – The silent environmental challenge - Jelčić Dubček, Dajana (Crisis Management Days, 2025)
Artificial satellites are an indispensable part of modern society, enabling telecommunications, broadcasting, navigation, and precise timing systems. They also play a crucial role in Earth observations, such as air pollution, ocean health and oil spills, glacier melting and coastal sealevel rise, supporting scientific research on environmental changes (Copernicus Program, 2025; Envisat, 2012). However, the rapid expansion of satellite-based technologies in recent decades has also raised significant environmental concerns. Distant and silent, satellites are often overlooked, making it easy to ignore the growing number of objects orbiting Earth. This paper aims to raise awareness of the ecological and operational consequences of space debris accumulation. Since the launch of Sputnik in 1957, more than 20,000 satellites have been placed into Earth’s orbit. A major concern is the high proportion of inactive satellites, which now constitute nearly half of the orbiting ones (ESA, 2025). The defunct satellites, no longer controlled or in communication with Earth, are highly vulnerable to explosions, collisions and fragmentation, generating thousands of debris fragments that can persist in orbit for decades. Incidents such as the 2009 Iridium 33-Kosmos 2251 collision and the unexpected loss of contact and the uncontrolled drift of the 8-ton Envisat satellite illustrate such hazard (Nicholas, 2009; Envisat, 2012). Currently, scientists track over 40,000 space debris objects larger than 10 cm and estimate more than a million smaller fragments (EESA Space debris office, 2024). Travelling at velocities of several kilometers per second, they are fast enough to cause severe damage to operational spacecrafts. The Kessler syndrome, a cascading chain reaction of collisions, once only a theoretical scenario (Kessler, 1978), is now an increasing risk, with the fast expansion of commercial satellite constellations further exacerbating this trend. While many modern satellites are now designed for controlled deorbiting and collision avoidance, proposed solutions include mission-extension vehicles that prolong satellite functionality, as well as active capturing systems that enable targeted atmospheric re-entries of the existing space-debris. Global collaboration and strict adherence to international guidelines is essential to ensuring the long-term sustainability of space operations and the continued reliability of satellite-based services.